CMP-Neu5Ac Hydroxylase Null Mice as a Model for Studying Metabolic Disorders Caused by the Evolutionary Loss of Neu5Gc in Humans. (19th October 2015) - Kwon, Deug-Nam; Choi, Yun-Jung; Cho, Ssang-Goo; Park, Chankyu; Seo, Han Geuk; Song, Hyuk; Kim, Jin-Hoi
Abstract : The purpose of this study was to identify the modification/turnover of gene products that are altered in humans due to evolutionary loss of Neu5Gc. CMP-Neu5Ac hydroxylase- ( Cmah -) deficient mice show the infiltration of Kupffer cells within liver sinusoids, whereas body and liver weight develop normally. Pathway analysis by use of Illumina MouseRef-8 v2 Expression BeadChip provided evidence that a number of biological pathways, including the glycolysis, gluconeogenesis, TCA cycle, and pentose phosphate pathways, as well as glycogen metabolism-related gene expression, were significantly upregulated in Cmah -null mice. The intracellular glucose supply in Cmah -null mice resulted in mitochondrial dysfunction, oxidative stress, and the advanced glycation end products accumulation that could further induce oxidative stress. Finally, low sirtuin-1 and sirtuin-3 gene expressions due to higher NADH/NAD in Cmah -null mice decreased Foxo-1 and MnSOD gene expression, suggesting that oxidative stress may result in mitochondrial dysfunction in Cmah -null mouse. The present study suggests that mice with CMAH deficiency can be taken as an important model for studying metabolic disorders in humans.